A classroom intervention to improve executive functions in late primary school children: Too 'old' for improvements?. (26th June 2018) - Benzing, Valentin; Schmidt, Mirko; Jäger, Katja; Egger, Fabienne; Conzelmann, Achim; Roebers, Claudia M.
Abstract : Background: Given the strong relationship between executive functions and academic achievement, there has been great interest in improving executive functions. School‐based group interventions targeting executive functions revealed encouraging results in preschoolers and young school children; however, there is a paucity of studies in older primary school children (age 10–12). This is surprising considering that deficits in executive function performance can often be observed in this age group. Aims: Therefore, the aim of this study was to examine whether an innovative customized school‐based group intervention could improve core executive functions (updating, inhibition, and shifting) in the age group concerned. Sample: In total, 118 ten‐ to twelve‐year‐old school children were recruited from eight participating classes. Methods: They were randomly assigned to one of two‐six‐week conditions of either a cognitive games group comprising of card and board games training executive functions (experimental group) or a wait‐list control group (regular school lessons). In the cognitive games group, the class teachers held a 30‐min training session twice a week. ANCOVAs (using pre‐test values as covariate) were used to compare executive function performance between groups. Results: Results revealed that the cognitive games group improved specific executive functions (updating and shifting) compared to the control group. These findings indicate that a school‐based group intervention can improve executive functions, even in 'older' primary school children. Conclusion: This study provides empirical evidence for the effectiveness of a classroom‐based cognitive training in older primary school children and is of practical relevance for educators.